Current panorama of tobacco use disorder - Ismael Sosa González; José Alejandro Ávila Cabreja; Ricardo González Menéndez; Haydée Fernández Massip; Raydel Conesa Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Tobacco is one of the most consumed legal drugs in the world, and cigar is the most common form of consumption. Cuba has the highest figures compared to the rest of the Caribbean countries, reason for which smoking is a major health problem. Due to this and the new discoveries related to this field, a bibliographic review was conducted to show the updated findings about the tobacco use disorder, or smoking. This was supported on the review of more than 60 documentary sources, 55 of them were taken as a bibliographic reference. The neurophysiological mechanisms involved are the activation of RnAc α4β2, and to a lesser extent, α6β2. The diagnosis is made through the guidelines established by the American Psychiatric Society. The effects of nicotine on the body include damage to the cardiovascular, respiratory, hematological, endocrine, and nervous systems. Although there are still unexplored areas, the treatment, from the psychosocial point of view and pharmacological, has achieved good results.